TREFOIL FACTOR FAMILY 1 EXPRESSION CORRELATES WITH CLINICAL OUTCOME IN PATIENTS WITH RETINOBLASTOMA. Issue 12 (December 2018) - Busch, Maike; Metz, Klaus; Beier, Manfred; Biewald, Eva; Dünker, Nicole
Abstract : Purpose: Correlation of trefoil factor family 1 (TFF1) expression in retinoblastoma tumors with different clinical parameters to evaluate a potential involvement of TFF1 in tumor development and progression. Methods: A representative cohort of 59 enucleated eyes from individual patients with retinoblastoma was analyzed for its TFF1 expression profile by immuno staining and real-time PCR. Trefoil factor family 1 expression was correlated with demographics, laterality, tumor-node-metastasis stage, International Classification of Retinoblastoma, tumor differentiation level, and treatment. Results: According to our analysis, increased TFF1 expression significantly correlates with unilateral tumors diagnosed in older children and with poorly differentiated tumors and higher tumor-node-metastasis stages. Conclusion: This retrospective study reveals that unilateral tumors at a higher clinical tumor-node-metastasis stage and poorly differentiated tumor cells express significantly higher levels of TFF1 than those of differentiated tumors at lower tumor-node-metastasis stages. Besides, TFF1 expression correlates with the age of the patients at the time of tumor diagnosis. Our data indicate that TFF1 expression levels are potentially useful additional markers in the classification of tumor staging and prognosis of patients with retinoblastoma. Abstract : Trefoil family factor 1 expression levels in retinoblastoma correlate with laterality, age of diagnosis, differentiation level, and tumor-node-metastasis stage, indicating its potential involvement in the development and progression of this childhood tumor.